Museum Vleeshuis: biografie van een monument - Migom, Serge 1973-; Caremans, Clement; De Paepe, Timothy 1981-; De Vos, Annemie; Hoendervangers, Elke; Maes, Mirte (Kontich BAI, 2024)
'Het Vleeshuis', one of the most important monuments in Antwerp and even Flanders, has graced the skyline of the city on the Scheldt for more than five centuries. Since its opening in 1504, this impressive guildhall has fulfilled many roles: market hall, painter's studio, warehouse, opera house. Since 1913, 'Het Vleeshuis' has been a museum, at present completely dedicated to the rich musical life of Flanders. (Translated with DeepL.com)
Keywords: Museum Vleeshuis | Klank van de Stad (Antwerp, Belgium); 16th Century (1501-1600); History; Antwerp (Belgium)